The ruins of urban modernity - Mogultay, Utku (Bloomsbury Academic, 2018)
Introduction – Explorations and mappings – Learning from venice – Movements and machines – The white city – The urban frontier – The unreal city – A tale of three cities – The doleful city – Conclusion – Bibliography – Index
Includes bibliographical references (pages 209-219) and index
Keywords: City planning; City and town life; Urbanization